Survey on radioactive contamination in Beijing following the Japanese Fukushima nuclear accident - Lou, Yun; Wan, Ling; Ma, Yongzhong; Li, Huijuan; Meng, Qinghua; Kong, Yuxia; Zhu, Weijie; Wu, Dapeng; Cui, Limeng (Journal of radiological protection, 2013)
The radioactive contamination in Beijing caused by the Japanese Fukushima nuclear accident was monitored. In this research, samples of air, rainwater, surface water and vegetables in Beijing were collected and measured to estimate the radioactive contamination levels in Beijing. During the period from the 15th to the 41st day after the first emission of radioactive material (first emission) from the Japanese Fukushima nuclear power station (NPS) on 12 March 2011, obvious radioactive contamination was found in the Beijing air samples. The maximum concentration of I-131 was 5.89 mBq m−3 in the air samples detected on the 22nd day after the first emission, and the maximum concentration of Cs-137 and Cs-134 was found on the 20th day after the first emission. Except for one sample of rainwater, no artificial radionuclides associated with Fukushima were found in surface water. The measurement results showed that there was no harm to the health of local Beijing residents.